Data Protection Laws - Alginahi, Hiba; Alginahi, Yasser M.; Kabir, M. Nomani (The Institution of Engineering and Technology (IET), 2019)
Data protection, data privacy, and information privacy are all terms defined as the process of protecting important data/information from corruption, scam, fraud, loss, or compromise. This includes the relationship between the data collection and technology, the public perception and expectation of privacy, and the political as well as legal roots surrounding that data. Therefore, data protection laws aim to provide a balance between the individual’s privacy rights and the proper use of data.